SAT-017 Relationship Between Vitamin D Levels and Signs of Polycystic Ovary Syndrome - Smykalova, Anastasia (J Endocr Soc, 2020)
An analysis of the structure of the causes of infertility shows that up to almost 25% of women of reproductive age ovulation disorders are observed. Hormonal disorders leading to the absence of ovulation, began to play a leading role in the etiology of infertility, special vitamin D deficiency, while today it has been established that its D receptors (VDR) are localized in most organs, including reproductive ones. VDR affect the expression of 1000 genes and play a crucial role in the implementation of sex hormones function. The aim of the study was to assess the vitamin D level in women of reproductive age, depending on the presence of signs of PCOS and waist circumference (WC). 71 women from 19 to 44 years old were examined of these, 41 patients were diagnosed with PCOS and impaired ovulatory function, in 30 patients the ovulatory cycle was preserved, and signs of PCOS were not detected. The level of vitamin 25 (OH) D3 in the serum of the subjects was evaluated by tandem chromato-mass spectrometry at the ArchiMed clinic of new medical technologies, Moscow. In the recommendations of the Canadian “The Vitamin D society”, 40-60 ng/ml the optimal level of serum vitamin D, a concentration of 20-40 ng/ml insufficiency, <20 ng/ml as a deficiency. Vitamin D deficiency was detected in 57% of women in both groups, with a pronounced deficiency (<10 ng/ml) in 17%, insufficiency was observed in 43% of cases, a sufficient level was not detected in any of the subjects. The average level of vitamin D in patients with PCOS was 18.2 (2 to 32.3) ng/ml, the value in patients without signs of PCOS was 18.5 (6.8 to 31) ng/ml. Comparison of the vitamin D value with WC showed that in women with PCOS with an WC <80 cm the value of this indicator was 18.8 ng/ml, and for WC ≥ 80 cm it was statistically significantly lower - 13.3 ng/ml (p<0.05). Conclusion. High prevalence of vitamin D deficiency among patients of reproductive age, with no differences in the magnitude of this indicator depending on the presence of signs of PCOS and persistent ovulation. Difference was established between the levels of vitamin D in patients with PCOS depending on the waist circumference - its insufficiency increases with an increase in WC. The results of the study suggest that the deficiency of vitamin D in the body increases with the aggravation of hormonal dysfunction in PCOS, which should be taken into account by specialists during the management of this category of patients and the treatment of infertility.